The insertion of Chinese National Oil Companies in Latin America - Martínez Ruiz, Itzel (2016)
The government of the PRC has moved its concern to safeguard its oil security to its development policies. This is reflected in its foreign policy and the management of its diplomatic relations and strategic alliances. Even though, the insertion of the Chinese oil companies overseas is not the main oil supply line, it is a long-term strategy which involve joint cooperation and coordination between the Chinese government, the oil state companies, the receiver government, as well as its respective oil companies. Taking into consideration this scenario, the main objective of this investigation is answer the following questions: What is? When did it start? which are the implications? and which are the benefits that the PRCh obtains with the insertion of its oil companies overseas.